Design and efficiency improvement of eco-conscious Sr3PBr3 and Sr3NCl3 double perovskite solar cells with IGZO and Cu2O as ETL and HTL - Md．Shamim Reza; Avijit Ghosh; Md．Selim Reza; Shafaiet Newaz Wornob; Sabina Sultana (Energy Nexus)
This research presents a new design for double perovskite solar cells (DPSCs) utilizing Sr3PBr3 and Sr3NCl3, which is noted for its enhanced stability in comparison to conventional single perovskite materials, thereby making it ideal for the development of ultra-thin, very efficient solar cells. The proposed architecture features a distinctive arrangement: Al/FTO/IGZO/Sr3PBr3/Sr3NCl3/Cu2O/Au. The study provides an in-depth theoretical examination of the energy band structure, defect properties, and quantum efficiency of the DPSC, focusing on the optimized photovoltaic (PV) specifications. Remarkably, the optimized DPSC achieves a power conversion efficiency (PCE), an open-circuit voltage (VOC), a short-circuit current density (JSC), and a fill factor (FF) of 32.46 %, 1.40 V, 26.51 mA/cm2, 87.26 %. Whereas without HTL, the PV parameters are PCE of 30.34 %, VOC of 1.27 V, JSC of 26.45 mA/cm2, and FF of 90.14 %. The impressive efficiency of 32.46 % is due to better charge extraction, improved alignment between the absorber and transport layers, and reduced losses from recombination. The double perovskite absorber's special characteristics, along with accurate doping and defect technology, allow for effective charge transfer and collection. Additionally, the research explores the influence of various factors such as temperature, interface defects, rates of carrier production and recombination, and the work functions of return contact materials on performance. The results underscore the significant potential of Sr3PBr3 and Sr3NCl3, especially when combined with the Cu2O HTL, in effectively reducing sheet resistance and enhancing overall solar cell efficiency. Validation of the design was performed using SCAPS-1D simulation software.